FACTORS AFFECTING THE CITY’S RESILIENCE TO FLOOD DISASTER IN EAST BANJARMASIN DISTRICT - Surjono; Fatmawati, Aisyah; Christia, Meidiana (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2023)
Resilience is a system that can fight and adapt to certain disturbances and recover its normal function or state of balance. Improving city resilience is essential for urban communities, especially for areas at risk of being hit by disasters. Based on data from the Banjarmasin City Government, the floods that hit almost the entire city of Banjarmasin had an inundation height of between 0.25 meters to more than 0.5 meters, and East Banjarmasin Subdistrict was the sub-district that had been submerged by flood inundation for the longest time and had the highest inundation height among other districts. The study aims to identify the factors that influence community resilience to floods and formulate a model to increase this resilience. The approach method used is to use a quantitative method with SEM-PLS analysis to determine the influencing factors and formulate a model for increasing the city’s resilience. The study results show that the factors influencing city resilience to floods are green open spaces, building shapes, income, insurance ownership, level of education, employment, beliefs, and norms.